CONSTRUCTION SAFETY THROUGH HOUSEKEEPING: THE HAWTHORNE EFFECT - Emmanuel Aboagye-Nimo; Fidelise EMUZE (Journal of Construction Project Management and Innovation)
Clean and tidy sites have often been associated with positive safety cultures in construction. Poor housekeeping can result in the creation of additional hazards and dangers, in the form of protruding objects, which may also be sharp, and may result in situations that can lead to slips, trips, and falls on-site. They also create uneven ground levels, debris, and muddy conditions, which can all lead to an increase in accidents. Housekeeping also contributes to projects being finished in a timely manner, due to fewer distractions being created by what would otherwise be a chaotic situation. However, maintaining good housekeeping practices on-site has been known to be challenging, due to the rapid and complex nature of construction projects. In research that was conducted to explore the question “Why is housekeeping a continuing challenge in Lesotho construction?”, the final outcome of site visits and observations revealed the classic phenomenon of the Hawthorne effect. Without deliberate or intentional “interventionary” measures or demands for regulatory adherence, subsequent visits revealed a transformation in site practices, specifically in housekeeping. The Hawthorne effect refers to a change in behaviour by the subjects of a study due to their awareness of being observed. This effect does not necessarily refer to positive or negative outcomes. In this paper, the transformation that occurred with regard to workers’ practices is discussed critically in the context of this phenomenon. A key outcome of this discussion is whether housekeeping can be encouraged or improved using the notion of awareness of being observed. Finally, the ethicality of carrying out overt or covert observations is deliberated